High-Frequency Raman Analysis in Biological Tissues Using Dual-Wavelength Excitation Raman Spectroscopy. Issue 2 (February 2020) - He, Wencai; Li, Bolan; Yang, Shan
A dual-wavelength excitation Raman probe with laser inputs at 866 nm or 1064 nm is customized and integrated into a compact Raman spectrometer that is based on an InGaAs detector. Under 1064 nm illumination, the spectrometer detects fingerprint Raman signals below 2000 cm –1 . While under 866 nm illumination, the spectral range is extended to cover high-frequency region (2400–4000 cm –1 ) that includes major C–H and O–H Raman vibrations. We demonstrate that the dual excitation InGaAs Raman is beneficial in detecting high-frequency Raman signals, especially water contents in high-fluorescent biological samples such as human dental tissues, grape skin, and plum skin due to the suppressed fluorescence interference.